MEMAHAMI KONTRADIKSI HADIS EKSKUSI HUKUM MATI PELAKU MURTAD DALAM PARADIGMA FIKIH KONTEMPORER - Ahmad Ridwan (IAIN Kediri, 2018)
A study on contradictive hadith is popular with terms “ilmu mukhtalaf al-Hadisikh and mansu>kh (elimination), and al-tarji>h (priority). In a case of murtad person, the majority of riwayah mention the punishment is death execution. However, there is also a riwayat that explains the delay of death execution to give a chance for murtad person to do taubat. The contemporer shoolars (ulama) debate the death punishment for murtad person that is done in hurry. It is done to debate the authority of shahih hadith about death punishment for murtad person, but with the consideration of keeping the life balace in nation and religion. By prioritizing fiqh approach, this article tries to study hadith on punishment for murtad person through al-jam’u and uses an-Nakha